ANALYSIS OF SOYBEAN INVENTORY CONTROL AS RAW MATERIAL FOR KIZZ CRUNCHY TEMPE CHIPS - Annisa Agustina; Pandi Pardian; Yayat Sukayat (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
Inventory control of raw materials is very important at Zanada Tempe House so that soybeans can always be available without the need for additional inventory costs due to excess orders with an irregular schedule. Soybean raw materials that will be processed by Zanada Tempe House are only ordered based on estimated production needs, but have not implemented a certain inventory control model to maintain production success so that it remains economical. This study aims to determine the performance of the production process and control of soybean inventory as raw material for economical "Kizz Crunchy" chips at Zanada Tempe House. This research uses a qualitative design and case study method. All data were analyzed using descriptive analysis and the Economic Order Quantity (EOQ) method. The results showed that the total cost of inventory based on company policies was almost two times greater than the calculation using the Economic Order Quantity (EOQ) method. If the EOQ method can be applied, it is able to provide benefits because it can spend costs accurately and to a minimum, cost savings can be made up to 63%.